Book Review: Leaving Rules that Enforce Preconception - Pernilla Pergert (Grounded Theory Review: An International Journal, 2014)
Given that the dictum of no preconception is not new in GT, why did Glaser focus his attention so much on it to write a whole book on this topic? The dictum has been declared over and over again, for example in the chapter on Generating Theory in the seminal work of Glaser and Strauss (1967) and the chapters on Reading the Literature and Forcing the Data in Glaser’s (1998) book entitled “Doing grounded theory.” It might  be reasonable, then, for a reader to ask why this book is needed and whether the dictumshould not just be followed. The answer is that not allowing preconceptions to influence research is one of the greatest challenges and maybe even “the most difficult procedure of all” (Glaser, 2013, p. 133). Therefore, it is important to take it seriously; expanding on the issue is commendable and a welcomed contribution to the literature on classic GT.